BEHAVIORAL REACTIONS OF A JEALOUS PERSON AND FEATURES OF PSYCHOLOGICAL CORRECTION OF JEALOUSY IN MARRIAGE PARTNERS - Петяк, Олена Віталіївна (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2020)
The article discusses the features of psycho-correctional work to overcome the negative impact of jealousy in the family, depending on the types of behavioral reactions of the marriage partners and the varieties of jealousy themselves. The procedure of theoretical and methodological research was to collect, analyze and generalize information about the characteristics of the models of behavior of partners in situations of jealousy. For the purpose of empirical diagnosis of the type of behavior, the Communicative Responses to Jealousy (CRJ) methodology of L. Guerrero in adaptation of I. Furmanov and A. Vergeichik were used. The results of the study revealed the patterns of behavior of marriage partners in jealousy situations. Men and women exhibit different behaviors, sometimes quite the opposite. So, a significant percentage of men are more likely to distance themselves from their partner, begin to ignore her. One in five women studied expresses openly their negative emotions to men in situations of jealousy. The use of integrative communication is typical for 13.3% of men and 6.7% of women. The study showed that most men are aggressive towards their wives; it is typical for them to control their wives. The same number of male and female respondents claims that their jealousy is manifested in attempts to please the partner, to do something pleasant for him. The study also showed that women are more manipulated in situations of jealousy and have more contact with rivals than men. Summarizing the obtained theoretical and empirical data, we have formed the following conclusions. If a tendency to pathological jealousy is found, you should invite your partner to undergo psychotherapy. With the help of diagnostics, it is possible to determine the leading behavior in a situation of jealousy and carry out a psycho-correctional work corresponding to the clarified type. An analysis of psychological research and practical work with marriage partners showed that the most effective areas of work with jealousy are: rational-emotive therapy aimed at correcting irrational assessment models, norms, beliefs, ideas, and conclusions with replacing them with rational ones; psychodrama; monodrama; gestalt; game therapy